1994
DOI: 10.1109/10.277271
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive lung ventilation controller

Abstract: Closed loop control of ventilation is traditionally based on end-tidal or mean expired CO2. The controlled variables are the respiratory rate RR and the tidal volume VT. Neither patient size or lung mechanics were considered in previous approaches. Also the modes were not suitable for spontaneously breathing subjects. This report presents a new approach to closed loop controlled ventilation, called Adaptive Lung Ventilation (ALV). ALV is based on a pressure controlled ventilation mode suitable for paralyzed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(38 citation statements)
references
References 25 publications
1
35
0
2
Order By: Relevance
“…With similar results, Kirakli et al (39) reported a significant shorter duration of weaning with ASV than PSV in AECOPD patients [median (IQR) 24 (20-62) h versus 72 (24-144) h, p = 0.041]. ICU stay was also shorter in ASV group [median (IQR) 11 (6-15) days versus 13 (8)(9)(10)(11)(12)(13)(14) days, p = 0.5] but this difference was not statistically significant, while results from our study had significantly shorter LOS in ICU [median (IQR) 4 (2.5-9) days versus 6 (3-11) days, p < 0.001].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…With similar results, Kirakli et al (39) reported a significant shorter duration of weaning with ASV than PSV in AECOPD patients [median (IQR) 24 (20-62) h versus 72 (24-144) h, p = 0.041]. ICU stay was also shorter in ASV group [median (IQR) 11 (6-15) days versus 13 (8)(9)(10)(11)(12)(13)(14) days, p = 0.5] but this difference was not statistically significant, while results from our study had significantly shorter LOS in ICU [median (IQR) 4 (2.5-9) days versus 6 (3-11) days, p < 0.001].…”
Section: Discussionsupporting
confidence: 59%
“…Adaptive support ventilation (ASV), first described by Laubscher (10) , it relies on closedloop regulation of settings in response to changes in respiratory mechanics and spontaneous breathing, with wide-ranging, automated, pressure modes from pressure-controlled ventilation to pressure-support ventilation. (11)(12)(13)(14) Some studies have evaluated the use of ASV in weaning cardiac surgery patients and have shown a reduction in weaning time, a reduced need for arterial blood gas (ABG) analyses, and fewer ventilator adjustments.…”
Section: Introductionmentioning
confidence: 99%
“…• The introduction of a new mode of ventilation such as PAV 50 , ALV 28 or ARIS 5 is a long and difficult process. Therefore, we chose i) to ventilate patients with a standard ventilation mode, pressure support ventilation, largely used for weaning, and ii) to add heuristic knowledge to improve its use and to facilitate the weaning process.…”
Section: A Knowledge-based System Working In Closed-loopmentioning
confidence: 99%
“…Among the different systems proposed for implementing DCV [5,[15][16][17][18][19][20], ALVS exhibits the following suitable functional features [6,7]: 1) opportunity of applying any airways pressure waveform of clinical interest during the time of controlled breathing without distortions, i.e. identical to that selected;…”
Section: Methodsmentioning
confidence: 99%